2017
DOI: 10.1186/s12936-017-2120-5
|View full text |Cite
|
Sign up to set email alerts
|

Malaria early warning tool: linking inter-annual climate and malaria variability in northern Guadalcanal, Solomon Islands

Abstract: BackgroundMalaria control remains a significant challenge in the Solomon Islands. Despite progress made by local malaria control agencies over the past decade, case rates remain high in some areas of the country. Studies from around the world have confirmed important links between climate and malaria transmission. This study focuses on understanding the links between malaria and climate in Guadalcanal, Solomon Islands, with a view towards developing a climate-based monitoring and early warning for periods of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…This study used the auto.arima statement to build the SARIMA model, in which lag = 12. The optimal ARIMA model for Yunnan Province is (0,1,2) × (0,1,1) [12]. Moreover, the seasonal decomposition model was implemented using the stlf statement, and the optimal model is ARIMA (0,1,2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study used the auto.arima statement to build the SARIMA model, in which lag = 12. The optimal ARIMA model for Yunnan Province is (0,1,2) × (0,1,1) [12]. Moreover, the seasonal decomposition model was implemented using the stlf statement, and the optimal model is ARIMA (0,1,2).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the seasonal decomposition model was implemented using the stlf statement, and the optimal model is ARIMA (0,1,2). In addition, by using the nnetar statement, the BP-ANN model was established, and the optimal parameter set is "NNAR (12,1,3) [12] ". In the LSTM used in this study, the optimizer is RMSprop, the learning rate is 0.001, the loss function is MSE, and the number of hidden layers is 2.…”
Section: Resultsmentioning
confidence: 99%
“…Study results not only revealed clear rainfall thresholds, but significant lag associations between rainfall and increases in malaria incidence such that drier October-December periods are followed by higher malaria transmission periods in January-June. Based on these statistical relationships an experimental early warning system has been proposed for the Guadalcanal region of the Solomon Islands [109]. Chuang et al [110] used cross-wavelet coherence to evaluate the regional El Nino Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD) effects on dengue incidence and local climate variables for Taiwan.…”
Section: Enso and Health Forecastingmentioning
confidence: 99%
“…Armed with this knowledge, they demonstrate how statistical models and geographical information systems are applied by the Colombian health authorities to develop early warning systems for malaria. For the Solomon Islands in the western Pacific, where ENSO has clear impacts on rainfall as a disease sensitive climate variable, Smith et al [109] applied stepwise regression to analyse climate variables and climate-associated malaria transmission at different lag intervals in order to identify rainfall thresholds associated with malaria categorised into three incidence categories. Study results not only revealed clear rainfall thresholds, but significant lag associations between rainfall and increases in malaria incidence such that drier October-December periods are followed by higher malaria transmission periods in January-June.…”
Section: Enso and Health Forecastingmentioning
confidence: 99%
“…These are currently not explicitly included in the model as hydrometeorological factors provide a better means of studying temporal variability of mosquito habitats. However, variations in climate variables, such as rainfall, have been known to influence the risk of malaria, including in the Solomon Islands [ 26 , 35 ], and may offer some cost efficiencies to malaria control programmes through early warning systems [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%